Molybdenum trioxide decorated on tapered microfiber for mode-locked erbium-doped fiber laser - Mohd Yusoff, N.; Lee, H. K.; Ng, E. K.; Abas, A. F.; Alresheedi, M. T.; Zainol Abidin, N. H.; Mahdi, M. A. (Elsevier Editora, 2021)
This work demonstrates a simple and economical route of preparing molybdenum trioxide/polydimethylsiloxane composite saturable absorber (MoO3-SA) for ultrashort pulse generation. The average size of MoO3 used in this work was about 10 μm and conveniently prepared using standard bath sonication. The MoO3-SA was fabricated by depositing MoO3 composite on tapered microfiber structure of 10 μm waist diameter via spin coating technique. The modulation depth, saturation fluence and non-saturable loss of the fabricated MoO3-SA were measured to be 4.02%, 28.3 μJ/cm2 and 33.02%, respectively. The employment of the MoO3-SA in erbium-doped fiber laser was able to generate mode-locked pulses at a threshold pump power of 64.1 mW with a central wavelength of 1559.87 nm and an ultrashort pulse duration of 748 fs. Micrometer-sized materials are far simpler in preparation which relaxes tight requirements for SA fabrication compared to advanced nanomaterials.